A survey on software defined networking enabled smart buildings: Architecture, challenges and use cases. (1st July 2019) - Younus, Muhammad Usman; Islam, Saif ul; Ali, Ihsan; Khan, Suleman; Khan, Muhammad Khurram
Abstract: The rapid advancement of information and communication technologies (ICT) has drastically augmented the connectivity of actuators, computational elements and smart devices to the physical world. In this context, smart building (SB) serves as a significant domain to automatically handle and control the temperature, humidity, ventilation, safety, lighting, and other building's operations. Moreover, it plays a vital role in implementing the standards of enhanced living environments (ELE) and ambient assisted living (AAL). However, the extensive use of ICT and inflexible architecture of SB pose many challenges including heterogeneity of applications and Internet of things (IoT) devices, security, efficient networking architectures and protocols, energy efficiency, reliability and quality of service (QoS) provisioning. In this perspective, software defined networking (SDN) has gained great attention since it is being evolved as a programmable, and flexible networking framework. This paper is devoted to surveying the research work conducted on the integration of SDN to SB. Consequently, it provides a comprehensive review on SDN enabled SB, its architecture, taxonomy, communication protocols, and challenges for an immersive and interactive experience. It also presents a basic architecture of SDN over traditional networking. Moreover, SDN applications are also exploited to handle the issues of the wireless network. Furthermore, this paper demonstrates the use cases to explain the impact of SDN paradigm on the SBs.